1991
DOI: 10.1111/j.1469-8137.1991.tb00970.x
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular–arbuscular mycorrhizas respond to corn and soybean cropping history

Abstract: SUMMARYCommunities of vesicular-arbuscular (VA) mycorrhizal fungi were studied in a long-term crop rotation experiment at two locations (Waseca and Lamberton, Minnesota, USA). Spores of mycorrhizal fungi were counted and identified in experimental plots with a cropping history of either corn (Zea mays L.) or soybean \Glycine max (L.) Merrill], Mycorrhizal fungal communities were affected by both location and cropping history. At Waseca, Glomus aggregatum Schenck & Smith, G. leptotichum Schenck & Smith and G. o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
2
11

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(87 citation statements)
references
References 38 publications
8
66
2
11
Order By: Relevance
“…The density of AM fungi as measured by per cent colonization and total spore count, fi rst increased with time since abandonment and then decreased in the late successional forest sites [20]. Our results on two age groups of G. biloba trees can be considered as early and late successional stages, respectively, show consistency with the above.…”
Section: Discussionsupporting
confidence: 88%
“…The density of AM fungi as measured by per cent colonization and total spore count, fi rst increased with time since abandonment and then decreased in the late successional forest sites [20]. Our results on two age groups of G. biloba trees can be considered as early and late successional stages, respectively, show consistency with the above.…”
Section: Discussionsupporting
confidence: 88%
“…This was perhaps due to higher phosphorus levels in soil which could inhibit the development and colonization of AMF (Abbott and Robson, 1984). According to previous studies, AMF colonization by roots is influenced by several factors including soil properties, soil water content, plant phenology, predation and propagule availability (Anderson et al, 1984;Johnson et al, 1991;Anderson et al, 1994;Schultz et al, 2001;Muthukumar et al, 2003). Others suggested that AMF spore abundance do not always correlate with root colonization potential of AMF (Camargo-Ricalde and Dhilion 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identi ed patterns consistent with negative feedback through the AM fungal community ( Johnson et al 1991;Bever 1994;Kiers et al 2000). However, in each case, accumulation of host-speci c root pathogens provides a likely alternative mechanism (Mills & Bever 1998;Bever 2002).…”
Section: Introductionmentioning
confidence: 99%